PENGARUH E-SERVICE QUALITY DAN E-TRUST TERHADAP KEPUASANPENGGUNAAPLIKASI DANA (STUDI KASUS PADA MAHASISWA ANGKATAN 2025 FAKULTAS EKONOMI UNIVERSITAS NEGERI MEDAN) - Suci Ramadani; T. Teviana (STKIP Subang, 2026)
This study aims to analyze the influence of e-service quality and e-trust on user satisfaction of the DANA application, with a case study of the 2025 cohort students of the Faculty of Economics at Universitas Negeri Medan. The phenomenon of a cashless society and the intense competition among digital wallet platforms underline the importance of maintaining service quality and trust in order to sustain user satisfaction. The research method employed is a quantitative approach using a purposive sampling technique involving 100 respondents. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS 22.0 software. The results of the study indicate that partially, the e-service quality variable has a positive and significant effect on user satisfaction with a regression coefficient of 0.123. Likewise, the e-trust variable has a positive and highly significant influence that is more dominant on user satisfaction, with a regression coefficient of 0.783. Simultaneously, these two variables contribute 96.5% to user satisfaction, while the remaining percentage is influenced by other factors outside the scope of this study.